Medical management of neurogenic bladder with oral therapy - Cameron, Anne P. (Translational Andrology and Urology; Vol 5, No 1 (February 02, 2016): Translational Andrology and Urology (Controversies and Current Management of Adult Neurogenic Bladder), 2016)
This is a review of the most current literature on medical management of the neurogenic bladder (NGB) to treat detrusor overactivity (DO), improve bladder compliance and treat urinary incontinence. The use of antimuscarinics, alpha blockers, tricyclic antidepressants, desmopressin and mirabegron will be discussed along with combination therapy to improve efficacy. These medical therapies will be the focus of this review with surgical therapy and botulinum toxin injections being the subject of other articles in this series.